Logistics optimization at the construction site (Research, Society and Development, 2022)
Optimizing means creating more favorable conditions, or making the best possible use of a situation. On a construction site, optimization would be a way of investing in organization, planning and location of materials, equipment and employees. That is, always objectively seeking to perform all tasks in the best possible way, that is, with rational use of available resources such as labor, physical resources and financial resources, always managing so that everything is in the best place among the options. Always taking into account the specific routine of your construction site, that is, the reality of construction. The objective of this article was to highlight errors and successes in a library work, which can be highlighted through logistical methods. When analyzing all the points of the construction site and its layout, it is observed that the work in question was able to meet most of the observed points of the methodology used.